2020
DOI: 10.1002/jbt.22630
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates acute kidney injury in a dry‐heat environment by reducing oxidative stress and inflammation in a rat model

Abstract: Curcumin exhibits anti‐inflammatory and antioxidant activities. We investigated the protective effects of curcumin in a renal injury rat model under dry‐heat conditions. We divided Sprague‐Dawley rats into four groups: dry‐heat 0‐ (normal temperature control group), 50‐, 100‐, and 150‐minute groups. Each group was divided into five subgroups (n = 10): normal saline (NS), sodium carboxymethylcellulose (CMCNa), and curcumin pretreated low, medium, and high‐dose (50, 100, and 200 mg/kg, respectively) groups. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
2
9
0
2
Order By: Relevance
“…We demonstrated that Cur, Re and BJe administration, alone or in combination, reversed Cd-induced nephrotoxicity by reducing the elevated levels of creatinine and blood urea nitrogen in the serum of Cd-treated mice reaching the maxim effect with BJe 40 mg/kg and with both association Cur 50 mg/kg + Re 20 mg/kg + BJe 20 mg/kg and Cur 100 mg/kg + Re 20 mg/kg + BJe 40 mg/kg. This finding was in accordance with previous research showing the improvement of nephrotoxicity by Cur and Re in other experimental models [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…We demonstrated that Cur, Re and BJe administration, alone or in combination, reversed Cd-induced nephrotoxicity by reducing the elevated levels of creatinine and blood urea nitrogen in the serum of Cd-treated mice reaching the maxim effect with BJe 40 mg/kg and with both association Cur 50 mg/kg + Re 20 mg/kg + BJe 20 mg/kg and Cur 100 mg/kg + Re 20 mg/kg + BJe 40 mg/kg. This finding was in accordance with previous research showing the improvement of nephrotoxicity by Cur and Re in other experimental models [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…After 150 min, the core body temperature of the HS group reached above 40.5°C, and the dry-heat heatstroke rat model was successfully established. The process of model creation replicated our previous study [ 11 ]. All rats were subsequently anesthetized with 3% pentobarbital sodium and killed.…”
Section: Methodssupporting
confidence: 58%
“…Past studies have mostly been conducted in humid-heat environments, but, contrary to popular expectations, there is limited evidence of a positive correlation between high humidity and mortality [ 10 ]. However, exposure to a dry-heat environment increases the risk of heatstroke under the influence of dehydration and other adverse factors [ 11 ]. Therefore, viable methods for preventing and treating heatstroke combined with lung injury are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Like many supplements, studies using curcumin as an intervention for heat stress have not been performed in ruminant livestock to our knowledge. However, heat-stressed rats had less severe increases in renal TNFα, IL-6, and IL-1β expression when receiving oral supplementation of curcumin [ 138 ]. This was perhaps indicative of reduced inflammation in a broader range of tissues, as it also coincided with less muscle damage.…”
Section: The Role Of Inflammation In Heat Stressmentioning
confidence: 99%